The Politics Of Small Businesses Survival In A Competitive Market: Problems And Solutions - et. al., Efebeh Vincent Eseoghene, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The political nature of man has made stakeholders of small businesses to be involved in one survival strategies or the order which have left the equitable distribution of infrastructure and operations of businesses owners a challenge in these regards. The study tried to identify the various problems as well as solutions to the problems militating against the small-scale business politically. The sample subject of the study is the 10 entrepreneurs and 40 employees of small- scale business. The questionnaire is a major instrument used. Mean and the standard deviation was used to analyse responses The results of the study showed that government have put up a lot of support programme to promote small-enterprise business in the local government area under study but policies, programme application, mismanagement/misappropriation of fund hinders the growth of the small-scale business. It was recommended that government should collaborate with the industrialists of the various small-scale businesses to find out their financial, manpower and infrastructural facilities needs and satisfy them